Successful Use of Ketamine for Burst Suppression in Super Refractory Status Epilepticus Following Substance Abuse - Mutkule, Dnyaneshwar P. (Indian J Crit Care Med, 2018)
Status epilepticus is frequently encountered in neuro Intensive Care Units. It is a medical emergency and if not treated promptly can lead to severe brain damage and even death. Here, we present the case of a 18-year-old male with uncontrolled and unrelenting seizures with a rare etiology requiring ketamine infusion for burst suppression as it was resistant to thiopentone and midazolam infusions. The management of this case is presented in detail.